2021
DOI: 10.3389/fneur.2021.652931
|View full text |Cite
|
Sign up to set email alerts
|

High PYGL Expression Predicts Poor Prognosis in Human Gliomas

Abstract: Background: PYGL has been reported as a glycogen degradation-related gene, which is up-regulated in many tumors. This study was designed to investigate the predictive value of high PYGL expression in patients with gliomas through bioinformatics analysis of the gene transcriptome and the single-cell sequencing data.Methods: The gene transcriptome data of 595 glioma patients from the TCGA database and the single-cell RNA sequencing data of 7,930 GBM cells from the GEO database were included in the study. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…PYGL is a hypoxia metabolism‐related gene. In cancer cells, the PYGL‐regulated glycogen metabolism process produces nicotinamide adenine dinucleotide phosphate (NADPH), which can scavenge ROS (Zhao et al, 2021). Excess uric acid can act as an antioxidant that can effectively scavenge increased oxygen radicals in the body (Tasaki et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…PYGL is a hypoxia metabolism‐related gene. In cancer cells, the PYGL‐regulated glycogen metabolism process produces nicotinamide adenine dinucleotide phosphate (NADPH), which can scavenge ROS (Zhao et al, 2021). Excess uric acid can act as an antioxidant that can effectively scavenge increased oxygen radicals in the body (Tasaki et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that points to PYGL being involved in glycogen degradation ( Zhan et al, 2021 ). The hypoxia metabolism gene PYGL was discovered to be upregulated in many malignancies, including breast cancers and head and neck squamous cell carcinomas ( Kawakubo-Yasukochi et al, 2021 ; Zhao et al, 2021 ). The glycogen degradation mediated by PYGL has been hypothesized to sustain the growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…This was not found for protein expression on the TMA, potentially due to the exclusion of necrotic tumour areas. Recently a similar analysis of the TCGA database also showed that PYGL was prognostic [ 62 ]. The higher expression we found of the PYGL compared to PYGB in GBM stem-like cultures suggests a role in plasticity and tumorigenesis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%